CREATING SMART UNIVERSITIES AS A CHALLENGE TO MODERNITY - A.S. Seitbatkalova; Zh.P. Smailova (Academic Journal of Physical and Chemical Sciences, 2019)
The main trends in modern society is the rapid development of information and computer technologies (ICT), communication channels and means of transmission and exchange of information, the integration of knowledge and technology, an increase in the number of open innovations, the transition to new forms and methods of organizational activity. This brings the world to a new “evolutionary revolution”, transforming the information society into what is commonly called the term smart society. In the era of the information society, the most competitive will be universities that can implement the ideas of creating a smart university. The article discusses the international experience of foreign scientific communities in the study of the structure, properties and functions of smart universities. The problems of ensuring the competitiveness of universities by embedding the system of higher education in modern market conditions through the use of modern information and communication technologies and the transition from the traditional management structure to process management, as well as the conditions and nature of the introduction of changes in the educational system of the Republic of Kazakhstan are considered.